2021
DOI: 10.1155/2021/9138548
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus as Single-Agent Immunotherapy and Minimal Manifestation Status in Nonthymoma Myasthenia Gravis

Abstract: Background. Tacrolimus is a second-line immunosuppressant in myasthenia gravis (MG) therapy, which is mainly used in combination with corticosteroids to reduce steroid dose and maintain the effect of immunotherapy. However, few studies have focused on the effect of tacrolimus as single-agent immunotherapy on achieving minimal manifestation status (MMS). Thus, this study is aimed at exploring the efficacy and influencing factors of tacrolimus as single-agent immunotherapy in MG. Methods. Clinical data of 75 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
3
1
1
Order By: Relevance
“…Outcome measurements indicated tacrolimus non-inferior to other medications, consistent with one study on MG of Osserman grades III and IV ( 16 ). Although the positive effects here seemed weaker than several earlier studies that reported remission rates ≥ 64% ( 11 , 12 , 15 , 16 , 21 ), the differences could be explained by the already achieved improvement before baseline and relatively stable MG status at enrollment. Almost all the previous studies started with tacrolimus initiation, while the majority of our patients began with a notable duration of treatment; conceivably, there was less space for a positive effect to be displayed.…”
Section: Discussioncontrasting
confidence: 97%
“…Outcome measurements indicated tacrolimus non-inferior to other medications, consistent with one study on MG of Osserman grades III and IV ( 16 ). Although the positive effects here seemed weaker than several earlier studies that reported remission rates ≥ 64% ( 11 , 12 , 15 , 16 , 21 ), the differences could be explained by the already achieved improvement before baseline and relatively stable MG status at enrollment. Almost all the previous studies started with tacrolimus initiation, while the majority of our patients began with a notable duration of treatment; conceivably, there was less space for a positive effect to be displayed.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the application of these regimens could be limited due to their slow onset of action and adverse events 2,13 . Previous studies suggest treatment of tacrolimus in MG may circumvent these limitations 6–8,16 . Mono‐tacrolimus has been applied in membranous nephropathy, refractory ulcerative colitis and heart transplantation 17–21 .…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 13 Previous studies suggest treatment of tacrolimus in MG may circumvent these limitations. 6 , 7 , 8 , 16 Mono‐tacrolimus has been applied in membranous nephropathy, refractory ulcerative colitis and heart transplantation. 17 , 18 , 19 , 20 , 21 Our results demonstrated that mono‐tacrolimus therapy has fast action onset with minimum adverse events in MG. Tacrolimus exerts its effect by inhibiting the calcineurin activity and downregulating the transcription of inflammatory cytokines, which results in the suppression of T‐cells activity and antibody production in B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timektomija se sprovodila kod svih pacijenata sa timomom, kao i kod pacijenata mlađih od 50 godina sa generalizovanom formom AChR-pozitivne SAMG. Studija koja je ispitivala efikasnost timektomije (MGTX) je nedvosmisleno potvrdila da je ona efikasna kod pacijenata sa AChR MG mlađih od 65 godina i da u ovoj grupi ona rezultira boljim terapijskim ishodom, potrebom za manjim dozama steroida i ređom potrebom za dodatnim imunosupresivnim lekom 41 . Timektomiju je važno uraditi što ranije, a najbolje u prvih 6 meseci do dve godine nakon početka SAMG, jer je pokazano da u ovim slučajevima ona ima posebno povoljan efekat [20][21][22] .…”
Section: Terapija Samgunclassified